Examining the Correlation Analysis of Functional Movement Screening Test (Fms) with Upper Limb Function in Male (Amateur And Non-Amateur) Handball Players - AlAkrh, Hamid; Minoonejad, Hooman; Saidi, Fouad; Ardakani, Mohammad Karimizadeh; Sohrabi, Somaye (INSPIREE: Indonesian Sport Innovation Review, 2023)
The  purpose  of  the study. is to see if there's a link between of   male (Amateur and non-amateur) players  college of physical education & sports science Al-Qadisiyah University  functional sports screens (FMS) and upper limb function. Materials and methods. The competition attracted 100 volleyball players ranging in age from 18 to 25 years old. BMI is calculated as 60-75 kg for heights of 170-200 cm. Keep a digital record for later analysis. At least 3 months before to involvement, there is no history of musculoskeletal injury. The seven functional motor evaluation exercise modes (squat, hurdle step, overhead squat action, inline lunge, shoulder flexibility, straight leg elevation test, trunk stability push-up test) are employed as assessment tools for sports injury prevention. Questionnaire for the Assessment of Arm Disability (DASH). This test is used to assess upper limb function. There is a significant Pearson correlation coefficient. p≤0.05 is used to check whether there is a connection between variables. Results. Research results show that high scores for measuring arm injuries are different from performance screening test scores. (r=.178, P=0.01) There is a strong connection between them. Conclusions. Coaches and sports experts seem to believe that choosing the right exam for athletes is crucial.